Jabatan Rangkap Dalam Hukum Persaingan Usaha Di Indonesia Dan Amerika Serikat - Siti Anisah (Jurnal Hukum IUS QUIA IUSTUM, 2023)
Under the Indonesian Competition Law, interlocking directorate in companies is not absolutely prohibited. This is in contrast to the US Competition Law which prohibits it per se. Nevertheless, the enforcement of competition law for cases relating to interlocking directorate held in the two countries have similarities, namely that it is necessary to prove should there be any impacts on competition. For this reason, this research was conducted by proposing two questions, namely, first, how is the regulation of interlocking directorate in Indonesian and the US Competition Law? Second, how is the enforcement of competition law in regards to interlocking directorate in Indonesia and the US? This normative legal research uses statutory, conceptual, case, and comparative law approaches to answer the question. This study concludes that the US applies the per se illegal approach, whereas Indonesian Competition Law applies the rule of reason approach. However, in the application of the rule of reason approach in Indonesia, it was identified that there was a non-uniformity in the considerations of the Commission Council and KPPU's Decisions for cases of interlocking directorate. The non-uniformity referred to is related to whether or not there has been a violation of the prohibition of interlocking directorate and its impact on unfair competition. Even though the US uses the per se illegal approach, its application still causes controversy because there is a court opinion stating that proof of impact or contrary to all provisions of competition law is required for a violation of interlocking directorate.Key Words: Business competition law; dual positions; Indonesia; United States of America AbstrakJabatan rangkap di perusahaan tidak dilarang mutlak dalam konteks hukum persaingan usaha Indonesia. Hal ini berbeda dengan hukum persaingan usaha Amerika Serikat yang melarangnya secara per se. Meskipun demikian dalam penegakan hukum persaingan usaha untuk kasus-kasus jabatan rangkap di kedua negara tersebut memiliki persamaan, yaitu perlu dibuktikan adanya dampak terhadap persaingan. Untuk itu, penelitian ini dilakukan dengan dua pertanyaan yaitu, pertama, bagaimana pengaturan jabatan rangkap dalam hukum persaingan usaha Indonesia dan Amerika? Kedua, bagaimana penegakan hukum persaingan usaha terkait jabatan rangkap di Indonesia dan Amerika? Penelitian normatif ini menggunakan pendekatan perundang-undangan, konseptual, kasus, dan perbandingan hukum untuk menjawab pertanyaan ini. Penelitian ini menyimpulkan Amerika Serikat memilih pendekatan per se illegal, sebaliknya hukum persiangan usaha Indonesia memilih pendekatan rule of reason. Namun dalam penerapan pendekatan rule of reason di Indonesia, teridentifikasi ada ketidakseragaman pertimbangan Majelis Komisi dan Putusan KPPU untuk kasus-kasus jabatan rangkap. Ketidakseragaman dimaksud sehubungan dengan terbukti atau ada tidaknya pelanggaran terhadap larangan jabatan rangkap dan dampaknya pada persaingan usaha tidak sehat. Meski di Amerika Serikat menggunakan pendekatan per se illegal, namun penerapannya masih menimbulkan kontroversi, karena terdapat pendapat pengadilan yang menyatakan pembuktian adanya dampak atau bertentangan dengan segala ketentuan dari hukum persaingan usaha diperlukan untuk pelanggaran jabatan rangkap.Kata-kata Kunci: Hukum persaingan usaha; jabatan rangkap; Indonesia; Amerika Serikat